Penguatan Moderasi Beragama di Ruang Digital Berbasis Nilai Lokal Malaqbiq untuk Siswa Madrasah dan Pondok Pesantren Sulawesi Barat - Aldiawan; Fathiyah; Muhtar; Ryan Wahyudi; Thoha Mun’im Masykur; Heril Umam (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
This community service program aims to explore and enhance digital literacy among students from madrasahs and Islamic boarding schools, specifically those at MAN 1 Majene, DDI Baruga, Hasan Yamani Islamic Boarding School, and MAN 1 Polewali. In addition to improving digital competencies, this initiative also seeks to reinforce students’ understanding of religious moderation grounded in the local wisdom of Malaqbiq values. The program was implemented through a combination of counseling, workshops, and practical training. The first stage involved counseling sessions on digital literacy and the concept of religious moderation. The second stage continued with a workshop focusing on the use of visual communication tools through social media. The final stage consisted of mentoring sessions guiding students through the planning, production, and editing of digital content that promotes moderate religious messages. The results demonstrated significant improvements in students’ digital literacy and a deeper understanding of religious moderation rooted in cultural values. Participants were able to produce and disseminate content promoting tolerant religious perspectives across various digital platforms. By integrating local cultural values with modern digital media, this community engagement initiative offers a comprehensive and contextualized approach to strengthening youth involvement in religious discourse. This model is expected to serve as an inspiration for similar programs in other educational settings.